2005
DOI: 10.1161/01.hyp.0000171189.48911.18
|View full text |Cite
|
Sign up to set email alerts
|

Urine Albumin Excretion and Subclinical Cardiovascular Disease

Abstract: Abstract-We examined the association between urine albumin excretion (UAE) and common and internal carotid artery intima-media thickness (IMT), end-diastolic left ventricular (LV) mass, and coronary artery calcification (CAC) scores using data from the Multi-Ethnic Study of Atherosclerosis (MESA), a population-based study of 6814 adults aged 45 to 85 years without clinical cardiovascular disease (CVD). The mean age of the MESA participants was 62.7 years, 47% were male, and 15% had diabetes mellitus (DM). Sex-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
105
2
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(121 citation statements)
references
References 29 publications
12
105
2
2
Order By: Relevance
“…Several studies provide evidence of increased cardiovascular morbidity and mortality at urinary albumin excretion rates below the conventional cut-off point for microalbuminuria in the general population, in addition to patients with diabetes or hypertension. [5][6][7][8][9][10] Klausen et al 5 found that a UACR value above the upper quartile, that is, 4.8 mcg min À1 , is associated with an increased risk of coronary heart disease (relative risk 2.0; 95% CI 1.4-3.0) and death (relative risk 1.9; 95% CI 1.5-2.4), independent of age, sex, renal creatinine clearance, diabetes mellitus, hypertension, and plasma lipids in non-diabetic and non-hypertensive adults. In the MONICA/KORA substudy, 10 it was noted that UACR levels of 4-10 mg g À1 may be associated with increased cardiovascular risk, considering the results of several studies, including the Framingham Heart Study, even though this level is far below the currently used threshold of 30 mg g À1 UACR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies provide evidence of increased cardiovascular morbidity and mortality at urinary albumin excretion rates below the conventional cut-off point for microalbuminuria in the general population, in addition to patients with diabetes or hypertension. [5][6][7][8][9][10] Klausen et al 5 found that a UACR value above the upper quartile, that is, 4.8 mcg min À1 , is associated with an increased risk of coronary heart disease (relative risk 2.0; 95% CI 1.4-3.0) and death (relative risk 1.9; 95% CI 1.5-2.4), independent of age, sex, renal creatinine clearance, diabetes mellitus, hypertension, and plasma lipids in non-diabetic and non-hypertensive adults. In the MONICA/KORA substudy, 10 it was noted that UACR levels of 4-10 mg g À1 may be associated with increased cardiovascular risk, considering the results of several studies, including the Framingham Heart Study, even though this level is far below the currently used threshold of 30 mg g À1 UACR.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have provided evidence of increased cardiovascular morbidity and mortality when urinary albumin excretion rates are below the currently conventional cut-off point for microalbuminuria, among the general population as well as those with diabetes or hypertension. [5][6][7][8][9][10] Although the threshold level at which microalbuminuria is predictive of cardiovascular outcomes is getting lower, there is a paucity of data showing the relationship between low-grade albuminuria and renal risk.…”
Section: Introductionmentioning
confidence: 99%
“…The extent of CAC predicts the risk of CHD events. [18][19][20] Albuminuria among older (mean age 63 years) 21 but not younger adults (mean age 44 years) 22 and glomerular filtration rate (GFR) 23 are each associated with CAC presence and extent. Albuminuria is a potent predictor of future cardiovascular events, even among persons with a normal GFR.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that urinary albumin excretion reflects the presence of CVD among patients. 4 Elevated level of LDL signifies the severity of acute coronary syndromes. 5 High levels of serum LDL are seen in our study also.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the conventional risk factors for atherothrombotic disease aresmoking, hypertension, diabetes, dyslipidemia, and obesity 3 . Some of the emerging risk factors include -microalbuminuria 4 .…”
Section: Introductionmentioning
confidence: 99%